Scale up of biopolymer from shake flask to 20l stirred tank fermenter - Dilah, Kadir (2008)
This study is about the scaling up for production of poly-βhydroxybutyrate (PHB) from shake flask to 20 liter stirred tank fermenter. This scale-up operation used the method of constant volumetric transfer coefficient (K L a) of oxygen. K L a values were derived by fitting the dissolved oxygen tension (DOT) versus time on computer with two unknowns, namely K L a and the electrode mass transfer coefficient (Kap) of oxygen. The stirrer speed (RPM) and the air flow rate (A) in the 20 liter fermenter that produce the value of K L a found in the shake flask was approximated using trial and error method which is 200 rpm for both scale. A fermentation run in 20 liter fermenter using these values of rpm and A gave a PHB yield comparable to that achieved in shake flask. From the research work, the K L a for 500 ml shake flask and 20 l stirred tank fermenter were 0.2809 and 0.2564 respectively. Meanwhile the Kap for 500 ml shake flask and 20 l stirred tank fermenter were 0.0010 and 0.0008 respectively. The holding time for sterilization cycle is also calculated at 7.75 minutes which is recommended to make it longer for safety precautions. The results for cell dry weight of shake flask and 20 l fermentor are 7.15g/L and 6.90g/L respectively. Meanwhile, the PHB yield for shake flask and 20 l are 1.0190 g/L and 0.926 g/L respectively. From these results, it can be concluded that this research work had achieved its objectives.